Polydopamine-coated double emulsion capsules for on-demand drug release with reduced passive leakage - Hyojun Lee; Giyeong Nam; Daehoon Han (Scientific Reports)
Abstract Double emulsions (DEs) are widely explored in pharmaceuticals due to their ability to encapsulate both hydrophilic and hydrophobic drugs. However, their inherent instability limits their effectiveness in controlled drug delivery. Double emulsion capsules (DECs), formed by encapsulating DEs within a polymer shell, improve structural stability but still suffer from unintended drug diffusion due to the porous nature of polymeric shells. Polydopamine (PDA), a bioinspired polymer known for its strong adhesion, biocompatibility, and chemical stability, is a promising coating material for biomedical applications. However, research on its coating on DECs and its potential impact on passive leakage remains underexplored. Here we report PDA-coated DECs as an on-demand drug release system. The PDA coating effectively reduces passive leakage by forming an additional PDA layer on the DEC surface. Under optimized coating conditions, the passive leakage of coated DECs is ~ 20% lower than that of uncoated DECs for 8 days. Also, on-demand drug release is demonstrated through the photothermal effect of PDA, which enables localized heating under NIR laser irradiation. This study highlights PDA-coated DECs as a versatile drug delivery platform with enhanced stability, tunable release properties, and photothermal activation, making them promising for targeted drug delivery, implantable therapeutics, and precision medicine.